Kewenangan Penegakan Hukum Oleh Polisi Perairan Dan Udara Di Wilayah Perairan - Wattimena, Rovky Asyer (Postgraduate Program in Law, Universitas Pattimura, 2024)
Introduction: Law enforcement authority by water and air police in the waters of Aru Islands Regency needs to be exercised. The regulation of law enforcement in the territorial waters of Aru Islands Regency has issued a series of related laws and regulations. However, for some things it is felt that they still need to be supplemented with implementing regulations because there are many laws and regulations that give authority to different law enforcement parties in carrying out enforcement. law in Indonesian maritime territory so that there is often overlapping of the main duties and functions of each law enforcement officer at sea.Purposes of the Research: The purpose of this writing is to determine and analyze the authority of the maritime and air police in implementing law enforcement in the waters of the Aru Islands Regency.Methods of the Research: This research is normative legal research with the legal materials used in the research being primary, secondary and tertiary using library study techniques in the form of international legal regulations, scientific works and literature.Results of the Research: The results showed that Polairud has quite broad authority in maintaining security and order in water areas, but there are still several challenges in carrying out its duties, such as limited resources and coordination between institutions.